Karakter Ulul Albab - Labib, M. Dzaky; Suryani, Ira; Rangkuti, Khairina Habib; Harahap, Putri Hasanah; Hayati, Miftah; Pane, Fizri Aspika Putri (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The word Ulul albab if interpreted linguistically consists of two words that both contain good meanings, namely: the word Ulul and the word Al-albab, here the word Ulul means someone who has/has something different from the word Al-albab, namely someone who has/has many meanings. From the meaning of the word, we can take the meaning of Ibn Kathir where he stated that Ulul Albab is a person who has perfect reason and intelligence within him. From here the pronunciation in Ulul Al-bab does as many as 16 repetitions in the Qur'an. However, literally the meaning of ulul al-bab is still in public which is only explained briefly and not in depth, because it is only explained literally that ulul al-bab is someone who has reason and intelligence in him. In writing this has a goal which is a form of writing in the description of the understanding of the nature and also the characters in ulul albab. In this writing we use an easy method where we take the literature review method, which is to explore various reference sources in the form of books and journals. Therefore, the results of the research that has been carried out show that an ulul al-bab person is able to manage the time he has with the 2 earliest activities, namely thinking/thinking and also remembering, therefore from these two activities together and in tandem to be able to always remember Allah SWT in any situation and anywhere. In the Indonesian translation itself, the meaning of the word Ulul Al-bab is very often used, because Ulul Al-bab is very often interpreted as